2019
DOI: 10.2337/cd18-0006
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Assess Clinical Utility and User Experience of Professional Continuous Glucose Monitoring Among People With Type 2 Diabetes

Abstract: IN BRIEF Glucose variability is a potential independent risk factor of poor clinical outcome among people with diabetes, with adequate measurement technically difficult and cumbersome. For this study, a novel 14-day continuous sensor was used to assess glucose variability among people with type 2 diabetes (T2D). The aim was to characterize glucose profiles for up to 2 weeks in T2D and to survey device utilization in a standard clinical setting and its potential to collect clinically meaningful data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…The use of a two‐part CGM SMA demonstrated significant improvements in diabetes self‐efficacy and A1C. Previous literature has cited mean scores on the self‐efficacy survey tool as 5.17 ± 2.22, with increases in self‐efficacy scores by 0.12 to 0.49 points after participation in a six week small‐group DSMES program 20,21 . The baseline and follow‐up self‐efficacy scores of participants in our study were well above this range.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The use of a two‐part CGM SMA demonstrated significant improvements in diabetes self‐efficacy and A1C. Previous literature has cited mean scores on the self‐efficacy survey tool as 5.17 ± 2.22, with increases in self‐efficacy scores by 0.12 to 0.49 points after participation in a six week small‐group DSMES program 20,21 . The baseline and follow‐up self‐efficacy scores of participants in our study were well above this range.…”
Section: Discussionsupporting
confidence: 61%
“…A sample size of 19 participants per group were needed for an adequate power of 0.80 and an alpha of .05 to detect a 1 point change in mean scores. This survey has good reliability (Cronbach's α = .85) and test‐retest validity of 0.80 in the general adult diabetes population 20,21 . In this study, there was good internal consistency (Cronbach's α = .89).…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…Moreover, safety assessment confirmed that FGM technology is an effective and safe substitute for blood glucose monitoring, provided that the patient is confident in the use of the technology and has a minimum average sensor scanning of eight times per day [55]. In fact, FGM use seems to have a clinical good acceptance by patients with T2D and clinicians [56]. Using AGP derived from FGM downloading to review glycemic profiles and to consider treatment adjustments, is associated with significant reductions in HbA1c levels also in T2D subjects due to a rapid and sustained reduction of hyperglycemia [57,58].…”
Section: Cgm and T2dmentioning
confidence: 86%
“…Diabetes Mellitus (DM) merupakan sebuah penyakit, di mana kondisi kadar glukosa (gula sederhana) di dalam darah melebihi batas normal (Mahdiana, 2010). Variabilitas glukosa merupakan faktor risiko potensial independen dari hasil klinis yang buruk diantara orang dengan diabetes (Kurt Midyett, dkk, 2019). DM merupakan penyakit dengan segudang komplikasi.…”
Section: Pendahuluanunclassified